Mali : First Review Under the Extended Credit Facility Arrangement, Request for a Waiver of Nonobservance of a Performance Criterion and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Mali. (IMF Staff Country Reports; Country Report ;, 2020)
Security and social conditions in Mali have steadily deteriorated in recent years, especially in the central and northern regions. Implementation of the 2015 peace agreement is challenging, rendering the return of effective state control to these regions difficult. Rising security spending is putting pressure on priority social and development spending. Notwithstanding the difficult security situation, the Malian economy, largely concentrated in the South, has performed fairly well. A new three-year ECF arrangement in support of the authorities' medium-term development strategy (CREDD 2019-23) was approved on August 28, 2019.